Percursos interrompidos: um olhar sensível para a apropriação do Anhangabaú por meio da arte - Lessio, Danielle Alves (2019)
This dissertation presents the possibility of the public space being multiple and capable of hosting appropriations beyond the ones to which it was conditioned, evidencing the relevance of heterogeneous dynamics in the city. Thereby, a reflection is proposed on the various situations present in the Anhangabaú Valley and the potential of artistic interruptions in this space, that resist the ideal of continuous motility of pedestrians and vehicles and an ordered mindset, of being able to introduce sensitive views and questionings for the connections between individuals and public space. It is sought to understand how the defined spatial clipping is part of a kinetic structure in which interruption and non-accelerated rhythm are not desired and, in contrast, how some pause events may incite different body relations and perceptions. By acting as resistance and creating defamiliarization, such actions encourage the reflection of the observer and enable the promotion of new references for architecture and city projects. As case studies, we analyze three events of artistic interruption that occurred in the Valley and that addressed the change in the experience related to walking through this space, these are: Detetor de Ausências, by Rubens Mano (1994), installed on Viaduto do Chá, The Last Word is the Penultimate (A Última Palavra é a Penúltima), by Teatro da Vertigem (2008 and 2014), which took place in the Xavier Toledo underground passage, and the Ponte do Rio Anhangabaú, by the BijaRi collective (2013), which was executed along the Avenue São João axis.